Microglia-derived extracellular vesicles uncover early alterations of inflammatory signaling in Alzheimer’s disease - Chiara Bianchessi; Maria Serpente; Evelyn Ferri; Giulia Giudici; Marina Arcaro; Vittoria Borracci; Caterina Visconte; Francesca Buccellato; Luca Sacchi; Manuela Pintus; Beatrice Arosio; Andrea Arighi; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) is increasingly recognized as a neurodegenerative disorder associated with chronic low-grade inflammation and age-related immune dysregulation. Microglial-derived extracellular vesicles (MDEVs) are emerging as important mediators of neuroimmune communication and potential biomarkers reflecting pathological processes occurring within the central nervous system (CNS). However, how EV-associated inflammatory signalling changes across different stages of AD remains poorly understood. In this study, we characterized the inflammatory molecular profile of serum-derived MDEVs in 22 AD patients, 19 prodromal AD subjects, and 23 healthy controls (HC). Cytokine concentrations were also evaluated in paired serum and cerebrospinal fluid (CSF) samples to compare vesicle-associated and soluble inflammatory signals across biological compartments. MDEVs were isolated by size exclusion chromatography followed by TMEM119-based immunoenrichment. Cytokine quantification was performed using the Ella Simple Plex automated immunoassay platform. MDEVs from AD patients showed a generalized reduction in both pro- and anti-inflammatory cytokines compared to HC, including IL-1β, TNF-α, IL-2, IFN-γ, IL-6, IL-12p70, IL-10, and IL-4. Notably, several alterations were already detectable at the prodromal stage. In contrast, soluble cytokines in serum and CSF displayed a predominantly pro-inflammatory profile in AD patients, with increased levels of IL-1β, TNF-α, and IL-12p70. No significant correlations were observed between cytokine levels measured in MDEVs and those detected in serum or CSF. Overall, these findings support the presence of a compartment-specific reorganization of inflammatory signalling during AD progression. Early alterations in MDEV inflammatory cargo may reflect disrupted EV-mediated neuroimmune communication and highlight the potential of MDEVs as accessible peripheral biomarkers of neuroinflammatory processes in AD.

Peripheral microRNA signature in genetic frontotemporal dementia—findings from the GENFI initiative - Chiara Fenoglio; Maria Serpente; Marina Arcaro; Tiziana Carandini; Luca Sacchi; Manuela Pintus; Vittoria Borracci; Giulia Giudici; Marta Rigoni; Paola Muti; Laura Ghezzi; Arabella Bouzigues; et al. (GeroScience, 2026)
Frontotemporal dementia (FTD) is a neurodegenerative disease characterized by significant clinical and genetic heterogeneity, with approximately 40% of cases linked to hereditary genetic mutations, including MAPT , GRN , and C9ORF72 . Recently, microRNAs (miRNAs) have emerged as key regulators of cellular processes related to neurodegeneration and as potential biomarkers for FTD. However, their relevance in presymptomatic stages remains poorly understood. We conducted a miRNA expression analysis using TaqMan OpenArray® panels on blood samples collected from 171 individuals, including symptomatic mutation carriers (SMC), presymptomatic carriers (PMC), and healthy non-carriers (NC). Dysregulated miRNAs were validated and bioinformatic tools were used to identify potential associated molecular pathways. In C9ORF72 , miR-20b-5p and miR-223-5p were significantly upregulated in SMC (fold regulation over NC: 2.418 p = 0.0336 and 7.829 p < 0.0264 respectively) and PMC (5.518, p < 0.0001 and 3.941, p < 0.0001 respectively). In GRN mutation carriers, miR-28-3p was altered in both SMC and PMC (fold regulation over NC: 1.484 p < 0.050 and 3.287, p < 0.050). In MAPT mutation carriers, miR-28-5p, miR-192-3p, miR-25-3p, and miR-532-3p were altered only in SMC (fold regulation over NC: 1.496 p < 0.050, 1.911 p = 0.006, 1.468 p < 0.05, and 0.728 p < 0.05). Bioinformatic analysis revealed enrichment of pathways related to neurodegeneration and synapse impairment. These results suggest that miRNA expression levels are deregulated in mutated SMC, in C9ORF72 and GRN PMC. Notably, miR-20b-5p, miR-223-5p, and miR-28-3p were increased in preclinical stages of the disease, supporting their role as early biomarkers for C9ORF72 -FTD and GRN -FTD. Conversely, alterations in MAPT carriers appeared only in symptomatic stages, suggesting a different involvement in disease progression.